2017
DOI: 10.35808/ersj/748
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Co-creation Activities, Trust and Gender on Higher Education Marketing Performance

Abstract: This study attempts to analyze the effect of co-creation activities on satisfaction and its impact on loyalty, and to investigate the mediating role of co-creation value and trust, as well as the moderating role of personality traits and gender in higher education. This study took the sample from graduate students of master's degree in management program or Master of Business Administration (MBA). There were 18 universities from 10 cities in Indonesia involved in this study. The survey comprised of 590 respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 67 publications
3
16
0
Order By: Relevance
“…Students are more satisfied when participating in a joint learning experience and working with the university to enhance service offerings that are adapted to their needs. These results are in the line with extant research [10,49,50]. More importantly, as noted by previous studies [36], co-creating value facilities a meaningful and interactive dialogue between organizations and customers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Students are more satisfied when participating in a joint learning experience and working with the university to enhance service offerings that are adapted to their needs. These results are in the line with extant research [10,49,50]. More importantly, as noted by previous studies [36], co-creating value facilities a meaningful and interactive dialogue between organizations and customers.…”
Section: Discussionsupporting
confidence: 92%
“…Maxwell-Stuart et al [28] also indicated that students participating in the co-creation process in both academic and non-academic matters pertaining to student life see the entire student experience in a way that positively relates to student satisfaction. The link between student co-creation behavior and satisfaction has been confirmed in empirical research [49,50]. Therefore:…”
Section: Effect and Outcomes Of Co-creating Valuementioning
confidence: 67%
See 1 more Smart Citation
“…The recommendation of this process is one of the measures of HEI student satisfaction, as previous authors already claimed in the context of HI. Ueda & Nojima (2012) confirmed that students with higher levels of satisfaction will speak positively about their experiences and recommend to friends and family and care about the HEI reputation (Sutarso, Halim, Balqiah, & Tjiptoherijanto, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are in line with several previous studies conducted by Fianto et al (2014), Rivai and Wahyudi (2017) and Flavián et al (2005) who state that there is a significant influence between image and trust. According to Sutarso (2017), where trust is used as one of the research variables on marketing performance with significant results. The theory was advanced by Moorman et al in Ishak and Luthfi (2011) which defines trust as a willingness to depend on other parties who have been trusted.…”
Section: Discussionmentioning
confidence: 99%